Скульптура против архитектуры? - Rappaport, Alexander (проект байкал, 2007)
Many critics consider Richard Serra the leading sculptor of the 20th century. He is famous not only for inventing something new in sculpture (abstract sculpture compositions existed before him, having been opened by constructivist vanguard of the beginning of the 20th century). Material selections by Vladimir Tatlin and sculptures by Osip Tsadkin, as well as compositions by Henry Moor appeared before Serra. Serra is famous for transferring his works' accent from the works as they are, which could be installed in any place, to their environment. That is he saw in the sculpture a key to understanding the urban space. His crude metal sheets and profiles, rectangular and curvilinear, exceeding regular scale of sculpture, come closer to architecture. Richard Serra places them near architectural constructions as checkpoints of intermediate scale category of space located between so-called «street furniture» – lamp posts, stalls, fountains and benches – and buildings, especially huge modern ones. But the matter is not only in the scale. Serra's sculptures are not only abstract compositions that harmoniously add to the space with their spacious scale. They have some mystery, some implicit sense appearing before a pedestrian as an enigma. Their mystique opposes both street furniture and architecture. But first of all it opposes the historical sculpture with its enigma always overshadowed by historical or biographical topic. Krylov's sculpture in the Summer Garden or Minin and Pozharsky's monument on the Red Square do not strike us, because we know that those monuments are erected IN COMMEMORATION of prominent people, as fellow citizens' tribute to their great contribution to the national history. But the crude metal sheets welded at different angles – what are they for? Who needs them? As an art critic, Edward Goldman, said, fame came to Richard Serra in 1989, when the sculpture composition Tilted Arc erected eight years before it was demolished by request of the public, that did not understand its sense and was exasperated with the obvious absence of this sense. However, Serra sees his sculpture's sense not only in its filling a scale gap in the environment, but also in its instigating a man to think and to concern the environment and the space as a problem, linking this problem with a problem of human's being. Is there any other way to explain the public's indignation? Serra's sculpture compositions do not obstruct pedestrian flow and do not offend anyone's dignity or memory, do they? They act as Zen koans, as if mutely asking a spectator about the sense. Not knowing the answer, the citizen gets exasperated – not with his inability to answer, but with the sculptor (or city government), imposing this enigma to him. Only children are always happy to get an enigma. They like to train their mind in determining the sense, because they believe in the sense of being and consider themselves successors of this sense. A grown-up member of the state, both of a totalitarian one and of one with a market economy, loses this ability, believing neither in God nor in devil, neither in state officers nor in heroes. He only gets annoyed when reminded about a sense. This irritation can be explained in terms of a conflict between conviction in his right to freedom and real feeling of his fatality. He is not disposed to play with the world and the artist. He is willing only to take sedative pills, cheering drinks and all kinds of flattery. Seeing a hero made of bronze or cast iron, he feels free either to share his respect towards the hero, or to spit upon the false idol. In both cases the sense realized by him remains in his power. When this sense escapes, the illusion of his power disappears too, in other words the illusion of his rights in this world where he is kicked by those who have more power and rights. Reasoning from quite Utopian ideals of Democracy, Richard Serra believes that to train such play of mind is as necessary as to brush teeth or to button a shirt. A man with this ability not functioning falls out of the society, officially remaining its member though. But there is also another aspect – relation of such enigmas to architecture. Architecture differs from Richard Serra's sculptures not only in scale. The difference is also in the fact, that, being a plastic object like an abstract sculpture, architectural composition has social and functional status, and therefore it does not represent any special enigma. Looking at a grand construction we understand that it is a City Administration, or a Bank, or a Library, or a Museum, or… whatever having its own socially approved status and sense never doubted. So, one can treat it either with respect or with hatred, not losing the feeling of ability for sense orientation. But Serra's sculptures sometimes lead to this. Nevertheless, architecture has turned out to be sensitive to such things and it currently tries to propose an enigma to a citizen instead of suggesting its status. The Guggenheim Museum in Bilbao or the Hundertwasser Viennese House in this regard come closer to sculpture, as if crushing differences between architecture and fine arts and making needless an artistic gesture such as Serra's. The question is to what extent this architectural aping is appropriate. Or maybe it is better to leave the sense space to the sculptor, focusing on the senses peculiar to architecture, which are claimed neither by Serra nor by his possible progeny. Evidently Serra experienced those problems himself, appealing to the authorities and searching for their support. Probably he was looking for support not only as an artist in need of a client, but also as an artist confronting social determinancy of architecture in urban environment. Thus he was indirectly returning to architecture its sense space, which architecture is currently ready to play with, forgetting about its sense limits. So it is a big question: whether his sculpture does harm to architecture with its competition with the latter or releases it from plays that are not appropriate to it in order to perform its maybe more sublime mission – not only to ask but also to answer the questions on the sense of being? However, solution of this problem is to what extent architects and their clients are ready to give such answers, to what extent these answers are sincere and realistic, and to what extent the society is ready to ask itself about the sense of its own being. But it is another topic.